Health Dimensions of Human Well-being : An Exploration of Linkages and Major Issues - Singh, Ravi S.; Chothodi, Satheesh (National Geographical Journal of India, 2022)
Well-being is central to human existence. Its study is over half-a-decade old and has got enriched philosophically and empirically as indicated by the present state of discourse. It is very important issue for societies like India where a visible rural-urban gap is found in every respect. Improved state of human development is an indication of positive social transformation and better well-being state of individuals. Human well-being is a multi dimensional concept, which varies in space and time. The present paper attempts brief analysis of varied dimensions of well-being with special reference to health. The analyses and discussions are primarily based on published literature and secondary data sources